Negotiating Sexual Boundaries through Reality Shows: A Multimodal Study of Paraphilic Behaviours in Big Brother Naija - Gbadegesin, Victoria Oluwamayowa; Olufunwa, Harry Omobokun (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
Allegations in the public space persist that the Big Brother Naija (BBN) show glamorises sexual gratification. It is perceived to constantly rupture the conservative narratives that surround the public expression of sex in many Nigerian cultures. Interestingly, many of these opinions have not been empirically substantiated. The current study, therefore, explores the nature of sexual boundary negotiation, the communicative tools employed in the negotiation, and the forms of sexual gratification embedded in the show. The data for the study are videos from seasons two and three of Big Brother Naija, with excerpts and video stills used for exemplification. The analysis and discussions are explored relying on Multimodal Interaction Analysis (MIA). The findings illustrate that Big Brother Naija participants are prosumers who do not only produce content to negotiate sexual boundaries but also consume the content produced by other participants in the show for the same purpose. Exhibitionism and frotteurism are linked to content production while voyeurism is linked to content consumption. These sexual behaviours position the show as one aimed at deliberately stretching the sexual boundaries imposed by cultures, ethnicity and religion in Nigeria.